Sosialisasi Pelaporan Keuangan dan Pemasaran Produk EMKM Melalui Media Sosial Dan Marketplace di Kota Pekanbaru - Yani Zulvina; Ferdy Putra; Adhitya Agri Putra; Nanda Fito Mela (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2020)
Pekanbaru City, as a city that has a high business climate, also has a fairly good MSME business development. However, the Covid-19 pandemic that has plagued the last few months has had a negative impact on the economy, including the Micro, Small and Medium Enterprise (MSME) sector. Therefore, MSME needs to regulate its financial and marketing strategies by taking advantage of the digital-based EMKM product marketing and financial reporting system so that MSME's business can continue during this corona pandemic. The implementation of service activities is carried out by providing direct counseling and conducting questions and answers as well as discussions with MSME actors regarding the Socialization of Financial Reporting and MSME Product Marketing through Social Media and Marketplace. After providing counseling on MSME financial reporting and digital-based marketing, the people of Kota Tinggi Pekanbaru District have knowledge and can apply SAK EMKM-based bookkeeping and digital product marketing.